‘TERA ROOM NUMBER KYA HAI?’: DISCOURSE STRATEGIES IN CRICKET SLEDGING - kriishnan T.R., Murali (ShodhKosh: Journal of Visual and Performing Arts, 2025)
This study examines sledging in cricket as a complex linguistic event situated at the intersection of performance, power, and speech situations. Through the analysis of selected historical and contemporary sledging incidents—from Richard Nyren’s archaic banter to Shane Warne’s psychological edge over Daryl Cullinan—this paper makes use of a multi-theoretical approach incorporating Speech Act Theory, Politeness Theory, and Critical Discourse Analysis. It explores how utterances during high-stakes cricket matches function not merely as sports bravado but as performative speech acts intended to assert dominance, destabilize opponents, or negotiate power hierarchies. By foregrounding the linguistic function of these utterances and embedding them within cultural and historical frames, the study interrogates the ethical and sociolinguistic boundaries of verbal aggression in sport.